Predictors of Multiple Micronutrient Powder Intake Adherence among Children Aged 6-23 Months in Rasuwa District, Nepal: A Cross-sectional Study - Timalsina, Ashish; Paudel, Rajan; Upadhyaya, Dipak P; Bhattacharya, Sujay; Kuikel, Bihari S; Joshi, Naresh P; Adhikari, Sunil; Aung, Aye A (Journal of Institute of Medicine Nepal, 2020)
Introduction Breastfeeding would not be sufficient to meet the micronutrient requirement of children after six months and more prone to iron deficiency anemia. Micronutrient powder (MNP) can be mixed with semi-solid food to feed the children aged 6-23 months, contains 12 different micronutrients, one of the appropriate strategies. The study’s objective was to assess adherence to MNP and its predictors among children aged 6-23 months in Rasuwa district of Nepal. Methods A cross-sectional study was conducted in the Uttargaya rural and the Kalika rural municipality of Rasuwa district among 200 mothers of children aged 6-23 months who were fed MNP. Proportionate random sampling was used to select eligible mothers for interviews, and a semi-structured questionnaire was employed for data collection. Multivariate logistic regression was used to obtain adjusted odds ratio with 95% C.I. Results Sample mean was calculated among 155 mothers who received 60 sachets of MNPs;41.3% had adhered to 60 sachets intake of MNP. The mean age of the mother was 25. 29±5.3 years and the mean age of children was 14. 66±5.2 months. In bivariate analysis, the mother having one child less than five years (COR=0.5, 95% CI: 0.24-1.0) and MNP received from the health facility (COR=1.96, 95% CI: 1.02-3.76) were statically significant. Further, multivariate analysis, a mother who accepted the properties of MNP (AOR=2.52, 95% CI: 1.27-5.00), was associated with high adherence. Conclusion Acceptability of MNP by the mother is the key to increase adherence to MNP. The distribution of MNP from a health facility, tailored with nutrition education is essential to improve adherence to MNP.